The Quotative System in Spanish and English Youth Talk. A Contrastive Corpus-based Study - Palacios Martínez, Ignacio Miguel (Miscelánea: A Journal of English and American Studies, 2014)
The speech of teenagers is rich in narratives, with the direct reproduction of speech, thoughts, and non-lexical material often introduced through the use of quotatives. This paper aims to compare such quotative markers in English and Spanish.. Findings indicate that both Spanish and British teenagers make use of a wide range of specific quotatives in their speech. For example, in English go and (be) like prevail clearly over general reporting verbs such as say, think and ask. In Spanish, we also find a system of both general reporting verbs (decir, ‘say’, contar, ‘tell’,  preguntar ‘ask’) and those more typical of teenager speech (y yo…. ‘and I ...’, en plan ‘like’, es como “it's like”, saltar , ‘come up with’, etc). However, in Spanish the latter represent only 25 percent of the total, compared to almost 50 percent in English. Linguistic factors (grammatical person, aspect, tense, content of the quote) seem to constrain differently the choice and function of the quotatives observed in the teen talk of English and Spanish.
Keywords: Spoken language; youth language; quotatives; direct speech; grammaticalisation